Evolusi Bahasa Pemrograman (Evolution Of Programming Language) - Muhammad Taufiq Pratama (STMIK Mardira Indonesia, Bandung, 2014)
Programming language, such a technology, always change from time to time. Evolution of programming language can’t be released from its history. There have been always revision of a programming language, or any new programming language each decade, to fulfill human’s need which is getting complex. Thus, the quantity of revisions or new languages occured can’t be counted as easily anymore, hence reconstructing its history wouldn’t be an easy thing to do as well. Resoluting this case, the Conference on the History of Programming Languages (HOPL) were held twice in USA in 1978 and 1993. On the first conference, the conference committee decides thirteen languages which fulfill criteria such as: having been in use for at least 10 years, had significant influence, and were still in use. On the second conference, the chosen programming languages were presented by the author of each chosen programming language to be documented in detail, which the result becomes an internationally approved history base of programming language. Yet of course the documented programming languages range are only those which occurred ten years before the second conference were held, hence the programming languages which occurred after then weren’t documented by HOPL. Keywords: hopl; selection; conference